2023
DOI: 10.3390/children10010110
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Arts Therapies with Children and Adolescents—Editorial

Abstract: Arts therapy dates back to the mid-20th century [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…After screening titles and abstracts alone, 29 were selected for full-text screening. Of the 29 fulltext studies, 24 were excluded due to being non-interventional (10), art-based activities not meeting the definition of art therapy (8), non-pain related outcomes (5), and adult population (1). Five studies were included in the final analysis, and the results are reported below.…”
Section: General Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening titles and abstracts alone, 29 were selected for full-text screening. Of the 29 fulltext studies, 24 were excluded due to being non-interventional (10), art-based activities not meeting the definition of art therapy (8), non-pain related outcomes (5), and adult population (1). Five studies were included in the final analysis, and the results are reported below.…”
Section: General Overviewmentioning
confidence: 99%
“…Art therapy used in medical settings is focused on providing emotional support through the patient’s medical experiences and coping with physical pain and other psychosocial symptoms like anxiety and fear [ 8 ]. It goes beyond the use of visual art activities (e.g., drawing, colouring books) as a simple distraction technique during painful procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, strengthening programs for students who are identified as disabled can help them realize their social and academic potential by promoting appropriate social behavior and emotional development ( 41 , 42 ). In this way, the clinical work of art therapy is gradually expanding into education and special education environments ( 43 ).…”
Section: Introductionmentioning
confidence: 99%